Arctic marine mammal population status, sea ice habitat loss, and conservation recommendations for the 21st century. Issue 3 (17th March 2015) - Laidre, Kristin L.; Stern, Harry; Kovacs, Kit M.; Lowry, Lloyd; Moore, Sue E.; Regehr, Eric V.; Ferguson, Steven H.; Wiig, Øystein; Boveng, Peter; Angliss, Robyn P.; Born, Erik W.; Litovka, Dennis; et al.
Abstract: Arctic marine mammals (AMMs) are icons of climate change, largely because of their close association with sea ice. However, neither a circumpolar assessment of AMM status nor a standardized metric of sea ice habitat change is available. We summarized available data on abundance and trend for each AMM species and recognized subpopulation. We also examined species diversity, the extent of human use, and temporal trends in sea ice habitat for 12 regions of the Arctic by calculating the dates of spring sea ice retreat and fall sea ice advance from satellite data (1979–2013). Estimates of AMM abundance varied greatly in quality, and few studies were long enough for trend analysis. Of the AMM subpopulations, 78% (61 of 78) are legally harvested for subsistence purposes. Changes in sea ice phenology have been profound. In all regions except the Bering Sea, the duration of the summer (i.e., reduced ice) period increased by 5–10 weeks and by >20 weeks in the Barents Sea between 1979 and 2013. In light of generally poor data, the importance of human use, and forecasted environmental changes in the 21st century, we recommend the following for effective AMM conservation: maintain and improve comanagement by local, federal, and international partners; recognize spatial and temporal variability in AMM subpopulation response to climate change; implement monitoring programs with clear goals; mitigate cumulative impacts of increased human activity; and recognize the limits of current protected species legislation. Abstract : Estado de las Poblaciones de Mamíferos Marinos del Ártico, la Pérdida del Hábitats de Hielo Marino y Recomendaciones de Conservación para el Siglo XXI Resumen: Los mamíferos marinos del Ártico (MMA) son emblemas del cambio climático, principalmente por su asociación cercana con el hielo marino. Sin embargo, no se encuentran disponibles ni una evaluación circumpolar del estado de los MMA ni una medida estandarizada del cambio en el hábitat de hielo marino. Resumimos los datos disponibles sobre la abundancia y la tendencia de cada especie de MMA y reconocimos subpoblaciones. También examinamos la diversidad de especies, la extensión del uso por parte de los humanos y las tendencias temporales en el hábitat de hielo marino para doce regiones del Ártico al calcular las fechas del retroceso de los hielos en la primavera y de su avance en el otoño a partir de datos satelitales (1979–2013). Los estimados de abundancia de MMA variaron enormemente en calidad y pocos estudios fueron lo suficientemente largos como para realizar un análisis de tendencia. De las subpoblaciones de MMA, el 78% (61 de 78) son cazadas legalmente por razones de subsistencia. Los cambios en la fenología del hielo marino han sido profundos. En todas las regiones, salvo el Mar de Bering, la duración del periodo de verano (es decir, la reducción del hielo) incrementó por 5–10 semanas y por >20 semanas en el Mar de Barents entre 1979 y 2013. A razón de los datos generalmente pobres, la importancia del uso por parte de los humanos y los cambios ambientales pronosticados para el Siglo XX1, recomendamos lo siguiente para la conservación efectiva de los MMA: mantener y mejorar el co‐manejo por parte de los socios locales, federales e internacionales; reconocer la variabilidad temporal y espacial en la respuesta de las sub‐poblaciones de MMA al cambio climático; implementar el monitoreo de programas con objetivos claros; mitigar los impactos acumulativos del incremento de la actividad humana; y reconocer los límites de la legislación actual para las especies protegidas.